Determinants of Company Value: Empirical Study on Agricultural Sector Companies Listed on Indonesian Stock Exchange 2017-2022: Indonesian - Muhammad Adi Nugrahatama; Axel Giovanni; Wildan Yudhanto (Profesional Muda Cendekia Publishing, 2024)
This research aims to provide empirical evidence regarding the relationship between Capital Structure, Profitability and Company Growth on Company Value in Agricultural Sector Companies Listed on the Indonesia Stock Exchange (BEI) for the 2017-2022 Period. The number of company samples was carried out using a purposive sampling method, where the samples were selected based on criteria set by the researcher. The data was processed using multiple linear regression analysis techniques using Stata 14. The results of this research show that Capital Structure and Company Growth have a significant influence on Company Value, while Profitability does not have a significant influence on Company Value.